Colchicine and coronary heart disease risks: A meta-analysis of randomized controlled clinical trials - Ma, Zijun; Chen, Jun; Jin, Kaiqin; Chen, Xin (Frontiers in Cardiovascular Medicine, 2022)
Background Several trials have considered the safety and clinical benefits of colchicine as a treatment option for secondary prevention in patients with coronary atherosclerotic heart disease (CAD), but its safety and clinical benefits remain controversial. The purpose of this study was to explore the clinical benefits of colchicine, focusing on certain subgroups of patients. Methods Randomized controlled trials (RCTs) of colchicine in subjects with acute or chronic CAD compared with controls were included to assess all-cause mortality, non-cardiovascular mortality, gastrointestinal adverse effects, diarrhea, MACE, cardiovascular mortality, MI, stroke, and hemodynamic reconstruction. We analyzed the association of cardiovascular, mortality, and gastrointestinal risk with colchicine in all subjects. We also focused on the cardiovascular risk of colchicine in subgroups with different drug doses, different treatment durations, diabetes mellitus, and gender. Results This meta-analysis included 15 clinical RCTs, including 13539 subjects. Colchicine reduced the risk of MACE (RR: 0.65; 95% CI: 0.38-0.77, p heterogeneity <0.01; I2=70%; p<0.01), stroke (RR: 0.48; 95% CI: 0.30-0.76; p heterogeneity=0.52; I2=0%; p<0.01), MI by 40% (RR: 0.60; 95% CI: 0.43-0.83; p heterogeneity=0.01; I2=59%; p<0.01) and risk of re-vascularization (RR: 0.68; 95% CI: 0.56-0.83; p heterogeneity=0.17; I2=40%; p<0.01), but had no significant effect on risk of cardiovascular death and risk of all-cause mortality. In addition, colchicine increased the risk of gastrointestinal side effects and diarrhea. In a subgroup analysis, low-dose colchicine and treatment duration > 1 month reduced the risk of MACE, MI, stroke, and re-vascularization. The results showed that gender and diabetes did not have a specific effect on the risk of MACE. Conclusion Colchicine has a positive effect in reducing the incidence of MACE, MI, stroke and re-vascularization, but can increase the risk of gastrointestinal and diarrheal events. Low-dose colchicine significantly reduces the risk of MACE more than high-dose colchicine, and the benefits of long-term treatment are higher than those of short-term treatment. Overall, long-term low-dose colchicine treatment may significantly reduce the risk of cardiovascular events.